1994
DOI: 10.1002/cjce.5450720208
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of voidage profiles in spouted beds

Abstract: A fibre optic probe has been used to measure voidage profiles in the fountain, spout and annulus of spouted beds. The voidage in most of the annulus was found to be somewhat higher than the loose‐packed voidage and increased with increasing spouting gas flow rate, contrary to usual assumptions. There is a denser region in the annulus where the voidage was a little lower than the loose‐packed bed voidage. In the core of the fountain, the voidage decreased with height for low spouting gas flow rate, consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
112
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 14 publications
20
112
1
1
Order By: Relevance
“…For example, Kwauk 35 showed experimentally that the radial solids fraction of FCC catalyst particles in a 90 mm diameter riser decreased from the wall to the axis. This was also observed by He et al 36,37 who measured particle velocity and solids concentration in a spouted bed with a fiber optic probe; and also by Samuelsberg and Hjertager 38 who investigated the flow patterns in a circulating fluidized bed reactor, both numerically and experimentally using laser Doppler anemometry (LDA). In both of these latter studies it was also shown that the particle flux in the axial direction also decreases from the axis to the walls, which means that particles near the wall experience a greater residence time than particles in the bulk phase.…”
Section: Design Overviewsupporting
confidence: 62%
“…For example, Kwauk 35 showed experimentally that the radial solids fraction of FCC catalyst particles in a 90 mm diameter riser decreased from the wall to the axis. This was also observed by He et al 36,37 who measured particle velocity and solids concentration in a spouted bed with a fiber optic probe; and also by Samuelsberg and Hjertager 38 who investigated the flow patterns in a circulating fluidized bed reactor, both numerically and experimentally using laser Doppler anemometry (LDA). In both of these latter studies it was also shown that the particle flux in the axial direction also decreases from the axis to the walls, which means that particles near the wall experience a greater residence time than particles in the bulk phase.…”
Section: Design Overviewsupporting
confidence: 62%
“…These results, along with others in the literature, raise a question about the semi-cylindrical spouted bed: are the measurements obtained using the half-bed technique truly representative for inferring the hydrodynamic data for cylindrical beds and, if so, for which variables? The studies by He et al (1994aHe et al ( , 1994b are conclusive regarding the velocity of the solid phase and the porosity of the bed, indicating that special care is necessary when applying this technique. Despite the need for special care, visual information related to the hydrodynamic behavior of the cylindrical bed can only be obtained using the half-column technique.…”
Section: Fig 1 Diagram Of a Semi-cylindrical (Half-column) Spouted Bedmentioning
confidence: 82%
“…They observed that inserting the flat wall into the bed changed the velocity profile of the particles due to the additional system friction caused by the wall. In addition to the above study, He et al (1994b) studied the behavior of the spouted bed porosity profile, comparing the results obtained for cylindrical and semi-cylindrical beds. It was verified that inserting the flat wall did not significantly change the porosity behavior of the bed in comparison with the change caused by the wall on the velocity profile of the solid.…”
Section: Fig 1 Diagram Of a Semi-cylindrical (Half-column) Spouted Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Nevertheless, techniques based on an optical-fiber probe are also promising for this purpose. [23][24][25][26][27][28][29] In recent years, with the development of high performance computers, researchers have used numerical methods to study the flow behavior of fluidized beds. [30][31][32][33][34][35] Computational fluid dynamic (CFD) modeling helps to explain the details of gas-fluidized bed hydrodynamics and allows developing quantitative process models that enable predictive scaling-up and process optimization.…”
mentioning
confidence: 99%